Data supporting the co-expression of PDHA1 gene and of its paralogue PDHA2 in somatic cells of a family - Pinheiro, Ana (2020)
This article presents a dataset proving the simultaneous presence of a 5′UTR-truncated PDHA1 mRNA and a full-length PDHA2 mRNA in the somatic cells of a PDC-deficient female patient and all members of her immediate family (parents and brother). We have designed a large set of primer pairs in order to perform detailed RT-PCR assays allowing the clear identification of both PDHA1 and PDHA2 mRNA species in somatic cells. In addition, two different experimental approaches were used to elucidate the copy number of PDHA1 gene in the patient and her mother. The interpretation and discussion of these data, along with further extensive experiments concerning the origin of this altered gene expression and its potential therapeutic consequences, can be found in “Complex genetic findings in a female patient with pyruvate dehydrogenase complex deficiency: null mutations in the PDHX gene associated with unusual expression of the testis-specific PDHA2 gene in her somatic cells” (A. Pinheiro, M.J. Silva, C. Florindo, et al., 2016).